Fresnes, « prison algérienne »*? (1954-1962) - Fanny Layani (L’Année du Maghreb)
During the Algerian War of Independence, Fresnes Prison, crux of the range of repressive measures in France, becomes essentially an Algerian prison, because of the French correctional administration’s policy of grouping together Algerian inmates, and because of Parisian courts’ across-the-board rulings of imprisonment. Fresnes helps us locate the precise turning points of the penitentiary issue during the war, particularly as it has produced a massive amount of archival material which, unlike most French prisons, has been largely preserved. Therefore, primarily at Fresnes does the problem arise about the prisoners’ status and their relationship both to French authorities and Algerian nationalist parties. The inmates strongly close ranks around two existing nationalist organizations, the National Liberation Front (FLN) and the National Algerian Movement (MNA), and Fresnes becomes the origin of widespread hunger strikes during the summer of 1959. Finally, this essay broaches the subject of prisoner politicization and capacity for group action, and the conditions of their potentially pursuing a measure of political activity behind bars.